A Parametric Model for Contribution of Superthermal Electrons to Oblique Measurement Electron Cyclotron Spectra Under ITER-Like Conditions. (4th July 2017) - Subhash, P. V.; Singh, Amit Kumar; Pandya, Hitesh; Divya, V. S.; Aparna, M. P.; Thanseem, T. K. Basitha
Abstract: For high-temperature tokamaks like ITER, electron cyclotron emission (ECE) measurements are expected to be affected by many factors like relativistic downshift, harmonics overlap, polarization scrambling, deviation of electron distribution from Maxwellian, etc. Many studies are already reported on the difference between ECE measurements and other measurements like Thomson scattering for existing high-temperature tokamaks like JET, TFTR, D-III-D, etc. As ITER is expected to reach a temperature of around 25 keV with a strong electron-ion coupling and additional heating, the deviation of the ECE radiation temperature from the electron temperature needs to be examined. This paper reports a parametric study on the effect of the presence of small superthermal populations on ECE measurements for ITER. A wide range of parametric space for superthermal parameters is used, assuming a bi-Maxwellian electron distribution, which obeys Kirchhoff law. The computational details and the results of the numerical studies are explained in this paper. Further, an attempt is also made to reconstruct the superthermal contributions from multiple oblique measurements, which is otherwise a difficult task. This reconstruction has been done through numerical calculations for two sets of measurements using detectors placed at same but opposite angles. Then, a scale factor is used to scale the difference between these two measurements to superthermal emission. The detailed procedure and possible physical explanations are presented. The dependence of this scale factor on the superthermal parameters is numerically studied, and a parametric equation is drafted between scale factor and superthermal parameters. The said equation contains two numerical constants, for which the values are numerically obtained from one set of simulations and verified with a number of calculations using different superthermal parameters.